BOOK REVIEW THE ARMY AND THE INDONESIAN GENOCIDE: MECHANICS OF MASS MURDER - Waagstein, Patricia Rinwigati (Indonesia Law Review, 2019)
The Army and Indonesian Genocide : Mechanics of Mass Murder is an extraordinarily detailed exploration by author Jess Melvin who aims to defy the common understanding of the 1965 ‘anti-communist’ purge which highlights the Indonesian army’s part in the arranging the related violence in Aceh, resulting as one of the first locations revolving around a series of widespread massacres in Indonesia. The book presents a unique narrative that ventures into the dismay found within the the history of the 1965 anti-communist movement in Aceh. Although other source materials mostly focus on the history of the 1965 anti-communist killings around more popular areas such as Java and Bali, this book in particular represents a limited number of research regarding the purge outside the confines of Java.